Evaluasi Efisiensi Proses Produksi pada Lintasan Original Equipment Manufacturing 1,2 di PT. XYZ - Sudjoko, Theofilus Calvin; Sutapa, I Nyoman (Jurnal Titra, 2019)
This research aim to improve the efficiency of the production proses on the OEM 1,2 line at PT. XYZ. This research conducted because of the large idle time and low efficiency found on the OEM 1,2 line. The method used to solve this problem is using line balancing method. The unit used as a measurement is Coil-Air Cooler Z0123348 (FRONIUS). The first step of the research is to take the cycle time from the production process of Coil-Air Cooler Z0123348. The next step is to determine the performance rating and allowance of the operator to get the standard time. The standard time is used as data processing to get the initial condition of the line and the improvements that will be given. The results of the design improvement show that the second improvement is the optimum solution. The calculation results show that with the second improvement, the idle time can decrease by 75.22% and the line efficiency increases by 22.86% with worker costs / unit Rp. 8.514, -.